Analyses on Clinical Efficacy of TIPS in the Treatment of Cirrhotic Portal Hypertension and Relevant Influencing Factors: Efficacy of TIPS on Cirrhotic Portal Hypertension - Liang, Zhihui; Li, liang; Cao, Liming; Liu, Jianyu; Liu, Jinglei (Cellular and Molecular Biology, 2022)
The study aimed to explore the clinical efficacy of transjugular intrahepatic portosystemic shunt (TIPS) in treating cirrhotic portal hypertension and relevant influencing factors. 100 patients with cirrhotic portal hypertension receiving TIPS in the 980 hospitals of PLA logistic force from January 2015 to January 2018 were enrolled. Blood was collected from patients to detect liver function indicators [aspartate aminotransferase (AST) and alanine aminotransferase (ALT)], renal function indicators [blood urea nitrogen (BUN) and creatinine (Cr)], glucose metabolism indicators [insulin and glucose (GLU)] and inflammatory factors [interleukin-6 (IL-6), IL-8 and CXCL9] before surgery and at1 and 6 month(s) after surgery. Surgical efficacy was evaluated. The physique of patients was examined. The portal venous pressure, diameter and hemorheological indicators of patients were measured. Additionally, postoperative complications and nursing satisfaction were observed. At 1 and 6 month(s) after an operation, the levels of AST, ALT, BUN, Cr, insulin, GLU and inflammatory factors IL-6, IL-8 and CXCL9 and the portal venous pressure were overtly reduced (p<0.05), the postoperative dry weight was increased (p<0.05), the postoperative nursing satisfaction was 97%, the patients with higher satisfaction had fewer complications (p<0.05), the diameter of the portal vein was notably lowered (p<0.05), while the blood flow rate was remarkably raised (p<0.05). After the application of TIPS in the treatment of cirrhotic portal hypertension, the liver function, renal function, glucose metabolism and portal venous pressure and flow rate of patients return to normal, and postoperative complications are clearly reduced after postoperative nursing, proving the overall efficacy. Hence, TIPS is worthy of popularization and application.